ChemInform Abstract: From the Sabatier Principle to a Predictive Theory of Transition‐Metal Heterogeneous Catalysis. Issue 34 (August 2015) - Medford, Andrew J.; Vojvodic, Aleksandra; Hummelshoej, Jens S.; Voss, Johannes; Abild‐Pedersen, Frank; Studt, Felix; Bligaard, Thomas; Nilsson, Anders; Noerskov, Jens K.
Abstract Review: 56 refs.